Kesan pendekatan pembelajaran konstruktivisme terhadap prestasi murid tahun 5 dalam mata pelajaran Bahasa Melayu di sebuah sekolah rendah, daerah Sandakan - Hasiah, Arjani (2011)
This study is an experimental survey that had been undertaken in a primary school in Sandakan district, Sabah. The purpose of this study is to know the learning impact of constructivism approach on Year Five pupil's achievement in Paper 1 Bahasa Melayu subject, especially in language system. Thee main aspects that studied namely from difference achievements of group, types of test, and gender gap differences. This three aspects tested on two groups which be different approach of lesson angle. Remedial group is an experimental group who had undergone in constructivism approach method. The duration is in eight weeks and the Treatment group will be approach by a traditional method created as comparison group from the aspect that studied. Respondent in this study consisting of 80 pupils including boy and girl inb year Five that divided into two groups and every group consisting of 40 pupils which differ in gender to every group. Treatment group consisting of 17 boys and 23 girls, while control group consisting of 27 boys and 13 girls. Instrument that used in this study is two sets objective question that conducted by two examination phase namely pre test and post test. Pre test given to both groups which aims to know readiness level and pupil present knowledge in Paper 1 Bahasa Melayu subject. Post test on the other hand given to both groups after expiry treatment group under go teaching and learning by using constructivism method approach in eight weeks of time. Information data that achieved were processed and analyzed by using software "Statistical Package For The Social Sciences" version 19.0 and description made based on descriptive analysis and T-test. The fascinating of this study is it would enhance the achievement significantly (t(39)= -14.274, p<.05) in Paper 1 Bahasa Melayu subject, compared to the achievement of treatment group that taught in traditional method. Apart from that, results of the study also showed significant differences in both types of test that governed through pre test and post test. This study also found no differences in gender that significant between pupils in treatment group in constructivism method approach